Socio-emotional competencies mobilized by nurse-leaders in coping with the covid-19 pandemic in a university hospital - Ises Adriana Reis dos Santos; Simone Coelho Amestoy; Gilberto Tadeu Reis da Silva; Marimeire Morais da Conceição; Patrícia Alves Galhardo Varanda; Vânia Marli Schubert Backes; Ingredy Nayara Chiacchio Silva; Olga Maria Brito dos Santos (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To understand the socio-emotional competencies mobilized by nurse leaders during and after facing the Covid-19 pandemic in a university hospital. Method: Case study, conducted with sixteen nurses working in the leadership of units and services at a university hospital in northeastern Brazil. Data collected in two moments through semi-structured interviews. The interviews took place between August to December 2022 and January to August 2023. An inductive and coded thematic analysis was performed, according to the bucket theme technique, assisted by the NVivo12 software and supported by the grouping of twenty-five items included in the Socio-emotional competence scale. Results: During the fight against the Covid-19 pandemic, nurses expressed a mix of emotions due to their lack of knowledge about the disease. Faced with the climate of fear and the feeling of helplessness, they developed strategies that minimized the risks of illness and death. Two categories emerged: Emotional climate experienced by nurses and Coping strategies developed by nurses in the context of the Covid-19 pandemic. Final considerations: The competencies of social awareness, regulation, self-control, creativity, and emotional awareness were identified in the nurses' reports. These skills contributed to coping with the pandemic period, through the participation, involvement, and integration of professionals.